2020
DOI: 10.1186/s41235-020-00218-5
|View full text |Cite
|
Sign up to set email alerts
|

Why does peer instruction benefit student learning?

Abstract: In peer instruction, instructors pose a challenging question to students, students answer the question individually, students work with a partner in the class to discuss their answers, and finally students answer the question again. A large body of evidence shows that peer instruction benefits student learning. To determine the mechanism for these benefits, we collected semester-long data from six classes, involving a total of 208 undergraduate students being asked a total of 86 different questions related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 91 publications
3
65
0
3
Order By: Relevance
“…The result would support previous work in this field. (Brooks and Koretsky, 2011;Bruck and Towns, 2009;Giuliodori, Lujan, & DiCarlo, 2006;Kaymak et al, 2019;Lasry et al 2009;Morgan & Wakefield, 2012;Porter et al, 2011b;Smith et al, 2009;Tullis andGoldstone,2020 Willoughby, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result would support previous work in this field. (Brooks and Koretsky, 2011;Bruck and Towns, 2009;Giuliodori, Lujan, & DiCarlo, 2006;Kaymak et al, 2019;Lasry et al 2009;Morgan & Wakefield, 2012;Porter et al, 2011b;Smith et al, 2009;Tullis andGoldstone,2020 Willoughby, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The peer discussion is the most well-known attribute of the PI model, and most of this review is given to reporting on learning Achievements observed after students' discussions. (Smith et al, 2009), (Porter et al, 2011b), (Bruck and Towns, 2009), (Lasry et al 2009), (Brooks and Koretsky, 2011), (Willoughby et al,, 2011), (Kaymak et al, 2019), (Tullis and Goldstone, 2020), (Morgan & Wakefield, 2012), (Giuliodori, Lujan, & DiCarlo, 2006) in their research they stated that after discussion, students ' wrong answers changed drastically to right answers.…”
Section: Introductionmentioning
confidence: 96%
“…However, when it comes to step 3 and 4, Elaastic engages learners in a peer rating phase before they submit their second answers. Even though quantitative studies [12,14,18] and the ICAP framework [3] emphasized the benefits of such interactivityrich processes , these 5 phases might not always be the best choice to orchestrate the sequence. Alternative options should be considered by teachers depending on learners' behavior and understanding.. To the best of our knowledge, Mazur's recommendation to skip phases 3 and 4 when less than 30% or more than 70% of learners' first answers are correct [12] is the only recommendation that can be found in literature (with few variations [19,11,5]).…”
Section: Technology-enhanced Formative Assessmentmentioning
confidence: 99%
“…. Based on this estimation, we define sequences as beneficial when d > 0 (which implies that p1 < p2) because it means that students understanding of the topic has been enhanced [18]. As suggested by Figure 2, the mean effect size decreases when the distance between p1 and 50% increases.…”
Section: Benefits Of Formative Assessment Sequences Increase When the Proportion Of Correct Answers Is Close To 50%mentioning
confidence: 99%
“…With two-votes-based processes, the number of students providing the correct answer at the fourth phase is expected to be higher than at the second phase. When this is the case, we qualify such sequence as beneficial because it means that students understanding of the topic has been enhanced [34].…”
Section: Introductionmentioning
confidence: 99%